2021
DOI: 10.1111/jfpp.15621
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel green pesticide system by using cold plasma to control Plodia interpunctella in pistachio

Abstract: One of pistachio export challenges is the damage of pistachio by warehouse pests (Mozaffari Nejad, 2011). One of the essential warehouse pests of pistachio is Plodia interpunctella (Hubner, 1813), which causes a lot of damage to this valuable product in pistachio storage (Ling et al., 2016).Warehouse pests are among the most critical problems in storing agricultural products that cause severe damage to crops after harvest until consumption in storage. The Indian meal moth (P. interpunctella) is a pest that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Xanthomonas, Ralstonia solanacearum) and pests (e.g. P. interpunctella, ants, birds) [11][12][13][14]. Combating these threats is essential as they can compromise agricultural production, nutritional contents and health safety [15].…”
Section: Influence Of Plasma On Seedsmentioning
confidence: 99%
“…Xanthomonas, Ralstonia solanacearum) and pests (e.g. P. interpunctella, ants, birds) [11][12][13][14]. Combating these threats is essential as they can compromise agricultural production, nutritional contents and health safety [15].…”
Section: Influence Of Plasma On Seedsmentioning
confidence: 99%
“…[18] showed that 100% mortality was achieved in the experimental population of T. confusum and E. kuehniella with plasma jet treatment of 20 sec. In a recent study, [19], reported an approximate duration of 14 min of atmospheric/argon cold plasma for complete destruction of Plodia interpunctella (Hu ¨bner) (Lepidoptera: Pyralidae) on pistachios. In another new study, [20] using two gases, argon and helium, showed that helium gas was more successful in controlling T. castaneum than argon gas and the best time to achieve the maximum mortality was 90 sec.…”
Section: Plos Onementioning
confidence: 99%
“…Both atmospheric and low-pressure plasma generating devices have been assessed for their effectiveness on pistachios: 1-5 log reductions of Aspergillus parasitucus [9], 2-5 log reductions of A. flavus [10][11][12][13], and 1-2 log reductions in the fungal population of naturally contaminated pistachios (range: 5.67-7.96 log CFU g −1 ) [14] have been measured, according to the device design, type of feeding gas (air, argon, sulfur hexafluoride), and exposure time. More recently, the effect of a plasma jet source on the warehouse pest of pistachio Plodia interpunctella has been evaluated as an alternative method of non-toxic pest control [15]. Even if the chemistry of the process is currently under investigation, it is a fact that plasma treatments showed strong potentials in mycotoxins degradation as well: [9] observed 20-50% reduction in the aflatoxin levels (B1, B2, G1, and G2), while [10] reported a 52% reduction of B1 toxin in pistachio nut samples.…”
Section: Introductionmentioning
confidence: 99%